2018
DOI: 10.3389/fpls.2018.00255
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Levels in Dicot Roots Are Determined by an Ancestral Symbiosis-Regulated Clade of the PHYTOENE SYNTHASE Gene Family

Abstract: Strigolactones (SLs) are apocarotenoid phytohormones synthesized from carotenoid precursors. They are produced most abundantly in roots for exudation into the rhizosphere to cope with mineral nutrient starvation through support of root symbionts. Abscisic acid (ABA) is another apocarotenoid phytohormone synthesized in roots, which is involved in responses to abiotic stress. Typically low carotenoid levels in roots raise the issue of precursor supply for the biosynthesis of these two apocarotenoids in this orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 78 publications
10
97
0
Order By: Relevance
“…For example, strigolactones are apocarotenoids derived from b-carotene that regulate plant architectural changes (Baz et al, 2018;Gao et al, 2018;Jia et al, 2018). These apocarotenoids inhibit shoot branching above ground and signal below ground with rhizosphere organisms to mediate root architectural changes necessary for symbiosis with beneficial mycorrhizal fungi and mediate resistance to harmful fungi (Al-Babili and Bouwmeester, 2015;Borghi et al, 2016;Decker et al, 2017;Stauder et al, 2018). Biosynthesis of strigolactones is regulated through PSY expression, subjected to feedback regulation and regulated in response to other plant hormones (e.g.…”
Section: The Bursting Field Of Apocarotenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, strigolactones are apocarotenoids derived from b-carotene that regulate plant architectural changes (Baz et al, 2018;Gao et al, 2018;Jia et al, 2018). These apocarotenoids inhibit shoot branching above ground and signal below ground with rhizosphere organisms to mediate root architectural changes necessary for symbiosis with beneficial mycorrhizal fungi and mediate resistance to harmful fungi (Al-Babili and Bouwmeester, 2015;Borghi et al, 2016;Decker et al, 2017;Stauder et al, 2018). Biosynthesis of strigolactones is regulated through PSY expression, subjected to feedback regulation and regulated in response to other plant hormones (e.g.…”
Section: The Bursting Field Of Apocarotenoidsmentioning
confidence: 99%
“…Biosynthesis of strigolactones is regulated through PSY expression, subjected to feedback regulation and regulated in response to other plant hormones (e.g. ABA, gibberellic acid, auxin) and to inorganic phosphate (Stauder et al, 2018;Jia et al, 2018). Strigolactone transport was shown to be mediated by an ABC transporter (Kretzschmar et al, 2012;Sasse et al, 2015).…”
Section: The Bursting Field Of Apocarotenoidsmentioning
confidence: 99%
“…Although Arabidopsis (Arabidopsis thaliana) contains only one PSY, there are two or three PSY isoforms in evolutionarily distant plants (Gallagher et al, 2004;Giorio et al, 2008;Li et al, 2008;Qin et al, 2011;Mlalazi et al, 2012;Fantini et al, 2013;Stauder et al, 2018;Ahrazem et al, 2019). PSY isozymes evolved following gene multiplication and exhibit functional divergence in response to developmental and physiological signals in plant tissues (Welsch et al, 2008;Ampomah-Dwamena et al, 2015;Stauder et al, 2018). However, it is not clear whether PSY isoforms have different enzyme activities and what amino acid residues in PSY sequences are critical for their activities.…”
mentioning
confidence: 99%
“…The up-regulation of SL content and release upon nutrient deficiency and during the AM symbiosis is mainly a result of increased transcript levels of SL biosynthesis genes, as shown for rice, Medicago truncatula and tomato (Bonneau et al, 2013;Sun et al, 2014;Wen et al, 2016;Stauder et al, 2018). Accordingly, sufficient phosphate availability reduces transcript levels of SL biosynthesis and transporter genes, as shown for petunia DAD1/CCD8 and the SL transporter gene PDR1 (Breuillin et al, 2010;Kretzschmar et al, 2012).…”
Section: Regulation By Nutrient Availabilitymentioning
confidence: 96%
“…Recently, it was shown that even the supply of carotenoid precursors (-carotene) for SL production is upregulated by phosphate starvation and during root colonization by AM fungi. This supply is mediated by a distinct symbiosis-inducible isoform of phytoene synthase and precursor supply can be limiting for SL production in dicot roots (Stauder et al, 2018).…”
Section: Regulation By Nutrient Availabilitymentioning
confidence: 99%